(1359) predicting the national freight transport demand an application of multivariate auto regressive moving average time series analysis - montasser, saadia H. (The Institute Of National Planning., 2018)
being forecast. In a previous study. in which the author took part , it had been suggested that Gross National' Product at constant prices would be about the most relevant single L variable affecting freight transport needs since most domestic product is physicality distributed within the economy.